B4galnt2-mediated host glycosylation influences the susceptibility to Citrobacter rodentium infection - Suwandi, Abdulhadi; Alvarez, Kris Gerard; Galeev, Alibek; Steck, Natalie; Riedel, Christian U.; Puente, José Luis; Baines, John F.; Grassl, Guntram A. (Frontiers in Microbiology, 2022)
Histo-blood group antigens in the intestinal mucosa play important roles in host–microbe interactions and modulate the susceptibility to enteric pathogens. The B4galnt2 gene, expressed in the GI tract of most mammals, including humans, encodes a beta-1,4-N-acetylgalactosaminyltransferase enzyme which catalyzes the last step in the biosynthesis of the Sd(a) and Cad blood group antigens by adding an N-acetylgalactosamine (GalNAc) residue to the precursor molecules. In our study, we found that loss of B4galnt2 expression is associated with increased susceptibility to Citrobacter rodentium infection, a murine model pathogen for human enteropathogenic Escherichia coli. We observed increased histopathological changes upon C. rodentium infection in mice lacking B4galnt2 compared to B4galnt2-expressing wild-type mice. In addition, wild-type mice cleared the C. rodentium infection faster than B4galnt2−/− knockout mice. It is known that C. rodentium uses its type 1 fimbriae adhesive subunit to bind specifically to D-mannose residues on mucosal cells. Flow cytometry analysis of intestinal epithelial cells showed the absence of GalNAc-modified glycans but an increase in mannosylated glycans in B4galnt2-deficient mice compared to B4galnt2-sufficient mice. Adhesion assays using intestinal epithelial organoid-derived monolayers revealed higher C. rodentium adherence to cells lacking B4galnt2 expression compared to wild-type cells which in turn was reduced in the absence of type I fimbriae. In summary, we show that B4galnt2 expression modulates the susceptibility to C. rodentium infection, which is partly mediated by fimbriae-mannose interaction.